2020
DOI: 10.1292/jvms.19-0605
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with rivaroxaban and monitoring of coagulation profiles in two dogs with venous thromboembolism

Abstract: Two dogs with immune-mediated hemolytic anemia complicated with thromboembolism were presented. Both of the dogs were initially treated with immunosuppressive therapy in conjunction with dalteparin and clopidogrel. Although the immunosuppressive therapy was effective, peritoneal effusion due to thromboembolism was observed during the course of the disease in these dogs. After initiation of rivaroxaban treatment, peritoneal effusion decreased immediately in parallel with the normalization of D-dimer, antithromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…The high rate (60%) of long‐term rethrombosis found in the present study and the high prevalence of hypercoagulability‐promoting chronic comorbidities found in this (71%) and other studies (42%‐77%) suggest that life‐long antithrombotic therapy, including platelet inhibition in conjunction with anticoagulation, might be justified for dogs after stent placement 2,3,5 . Although warfarin and rivaroxiban are safe and effective for treating thrombosis in dogs, no consensus currently exists for the prevention of rethrombosis in dogs 3,16,45‐49 …”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The high rate (60%) of long‐term rethrombosis found in the present study and the high prevalence of hypercoagulability‐promoting chronic comorbidities found in this (71%) and other studies (42%‐77%) suggest that life‐long antithrombotic therapy, including platelet inhibition in conjunction with anticoagulation, might be justified for dogs after stent placement 2,3,5 . Although warfarin and rivaroxiban are safe and effective for treating thrombosis in dogs, no consensus currently exists for the prevention of rethrombosis in dogs 3,16,45‐49 …”
Section: Discussionmentioning
confidence: 46%
“…2,3,5 Although warfarin and rivaroxiban are safe and effective for treating thrombosis in dogs, no consensus currently exists for the prevention of rethrombosis in dogs. 3,16,[45][46][47][48][49] Historically, prognosis for aortoiliac thrombosis has been grave with limited survival in acute and non-ambulatory cases, regardless of treatment. 2,3,5 In contrast, dogs that survived to discharge (5/7) in the current study, sustained a reasonable quality of life between 208 and 1053 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varias de las investigaciones realizadas recomiendan su uso, inclusive en gatos, sin presentar muchos efectos adversos, pudiendo evidenciarse en pocos de los casos ptialismo o vómitos [10,11]. En este estudio se utilizó una dosis de 2 mg•kg -1 cada 24h PO; difiriendo con Uchida y col. [30] quienes utilizaron clopidogrel a dosis de 3 mg•kg -1 cada 24h PO y 4,7 mg•kg -1 cada 24h para su dos pacientes reportados.…”
Section: Resultados Y Discusiónunclassified
“…La dosis empleada en el presente estudio (0,6 mg•kg -1 q24h PO) difiere a la usada por Andruzzi y col. [1], que fue de 1,3 mg•kg -1 q24h PO, la misma que disminuyeron a la mitad por los costos elevados. En otro estudio, realizado por Uchida y col. [30], empezaron con una dosis inicial de 0,8 mg•kg -1 q24h PO y la redujeron a 0,4 mg•kg -1 q24h, debido a que el paciente presentó hematuria (misma que se resolvió con la disminución de la dosis), asociada a insuficiencia renal, la resolución completa del trombo se suscitó a los 14 días post administración. Petzold y col. [20] demostraron que el rivaroxabán reduce el riesgo de infarto miocárdico en comparación con el uso de antiplaquetarios solos, además, de actuar como profiláctico en la aparición de tromboembolismo en estados hipercoagulables.…”
Section: Resultados Y Discusiónunclassified